Rancang Bangun Computer Assisted Instruction (CAI) Sebagai Media Pembelajaran Dalam Mata Pelajaran Fisika Sekolah Menengah Atas - Harjanto, Arif; Prahasto, Toni; Suhartono, Suhartono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Strategy of using of Computer Assisted Instruction (CAI) as learning media is needed for solving problems that rise in learning process. Good learning packaging give positive effect in improving human potency. CAI as learning media based on computer microprocessor is built as complement and support learning method that usually use lecturing method, information discussion, and presentation.  The goal of this research is design and build interactive learning media CAI by multimedia technology. Result of this research is CAI visualisation by tutorial model and simulation as physics learning media by computer for senior high school students, XI Grade. This research involve a number of 8 teachers and 90 student XI Grade as respondents. Respondents questionnaire result show that 91.11% of students state that CAI product is qualified, 75.11% of students state that material presentation are qualified, 95.11% of students state that CAI program can increase study motivation.Keywords : Computer Assisted Instruction (CAI); Learning Media; Multimedia; Physics.